Propuesta de un sistema de gestión de la seguridad y salud en el trabajo en la empresa M&M Ingeniería y Control del Aire S.A.S. de conformidad con el marco normativo colombiano (2021)
This undergraduate work establishes a proposal for the implementation of a System of Management of Safety and Health at Work, in accordance with the Colombian regulatory framework in the company M&M INGENIERÍA Y CONTROL DEL AIRE S.A.S., in the same way defines the minimum standards of the Occupational Safety and Health Management System , represented in the Deming cycle composed of the phases of (Plan, Do, Verify and Act), these are aimed at complying with the requirements of the legal and current regulations on Occupational Safety and Health.